Pengungkapan Biaya Lingkungan dalam mendorong Green Economy di Wisata Pantai Botutonuo - Nurmillah N Ali; Sahmin Noholo; Siti Pratiwi Husain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to reveal the environmental costs of Botutonuo Beach tourism in encouraging the Green Economy. This research method uses a qualitative descriptive method with a field study approach, where the researcher is the key instrument, the data collection technique is carried out by triangulation (combination), the data source in this research uses primary and secondary data. The informants for this research are Botutonuo Beach Tourism Managers and the Community . The research results show that the presentation of environmental costs in Botutonuo beach tourism is presented together with other costs which are recorded in the profit and loss financial report. Where the presentation of environmental costs arising from waste management activities is then disclosed in the operational report, this disclosure is useful for knowing the transactions that will be incurred. By business owners so that they can encourage the Green Economy in tourism.